Screening of total phenolic, antiradical and antioxidant activities of Wiedemannia orientalis - Turkoglu, Ismail (C M B Assoc, 2018)
In this study, it was aimed to investigate total phenolic, antioxidant and antiradical activities of water and ethanolic extracts of the Wiedemannia orientalis (W. orientalis). In order to investigate the antiradical capacities, DPPH and ABTS radical scavenging activates were employed in the evaluation process. For the evaluation of antioxidant capacities, activities of phosphomolybdenum assay, reducing power and metal chelating were investigated. In the evaluations, the amounts of total phenolics were determined to be 11.95 +/- 0.02-17.27 +/- 0.09 mg Gallic acid equivalents (GAE)/g in W. orientalis extracts, respectively. Additionally, the amount of reducing power and total antioxidant capacity of leaf ethanol extract of W. orientalis were determined to be higher compared to the other extracts of W. orientalis. While the highest activity was observed in flower ethanol extract on the DPPH radical scavenging activity, flower water extract demonstrated better results in metal chelating activity. In the ABTS radical chelating activity, no significant differences were observed. As a result, it was suggested in our study that extracts of W. orientalis could be regarded as a natural and alternative source in pharmacology and medicine and food sectors. Such results can be put to use in pharmaceutical formulations and may lead to the developments of new human drugs from this medicinal plant.
Keywords: Wiedemannia orientalis; Antiradical activity; Antioxidant activity; Phenolic